2020
DOI: 10.1177/0272431620983459
|View full text |Cite
|
Sign up to set email alerts
|

Family Socioeconomic Status, Educational Expectations, and Academic Achievement Among Chinese Rural-to-Urban Migrant Adolescents: The Protective Role of Subjective Socioeconomic Status

Abstract: The adverse impact of a low family socioeconomic status (SES) on rural-to-urban migrant children’s academic achievement has been widely demonstrated. However, knowledge regarding the mechanisms underlying this relationship is limited. The current study aimed to examine the potential mediating effects of educational expectations and the moderating effects of subjective SES on the relationship between family SES and academic achievement among Chinese rural-to-urban migrant adolescents. A sample of 321 rural-to-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 72 publications
2
17
0
1
Order By: Relevance
“…The studies that found positive associations between family SES and academic achievement collected data from several schools from different cities (Hascoet et al, 2021; Zhang et al, 2020). Meanwhile, we found that one study collected data from one school and showed that family SES was weakly correlated with test scores ( p = .05) (Ren et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The studies that found positive associations between family SES and academic achievement collected data from several schools from different cities (Hascoet et al, 2021; Zhang et al, 2020). Meanwhile, we found that one study collected data from one school and showed that family SES was weakly correlated with test scores ( p = .05) (Ren et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Almroth et al (2018) found that the odds of adolescents showing externalizing behaviors decreased dramatically when both the adolescents and their parents expected a university education compared with either the adolescents or the parents having expectations that were lower than a university education. Although these two studies were not conducted with Chinese adolescents, the positive role of parents’ educational expectations in adolescents’ academic and psychological outcomes that existed in these studies has also been found in Chinese society ( Long and Pang, 2016 ; Guo et al, 2018 ; Lv et al, 2018 ; Leung and Shek, 2019 ; Lu et al, 2020 ; Ren et al, 2021 ). Moreover, the suitability has been demonstrated of person–environment fit theory for Chinese society ( Jiang and Jiang, 2015 ; Wang and Wang, 2018 ; Liu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Educational expectations are realistic beliefs regarding future academic outcomes, such as the highest level of educational attainment ( Yamamoto and Holloway, 2010 ; Wang and Benner, 2014 ; Ren et al, 2021 ). Adolescents’ educational expectations are usually measured by asking them which educational level they expect to complete ( OECD, 2019 ; Ren et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations